Answer:
Here we have the function:
y = f(x) = 3^x
Using the values:
x and (x + 1)
We need to find that the y-value increases by a factor of 3.
So we need to prove that:
f(x + 1) = 3*f(x).
Or we can see the quotient:
f(x + 1)/f(x) = 3
Here we can find the values:
f(x + 1) = y = 3^(x + 1)
f(x) = y' = 3^x
If we take the quotient, we get:
![(f(x + 1))/(f(x)) = (3^(x + 1))/(3^x)](https://img.qammunity.org/2022/formulas/mathematics/high-school/s3zd53jrh1h1i3o72vzsb1d3imbtfmgsx0.png)
Here we can use the properties:
![a^n*a^m = a^(n + m)](https://img.qammunity.org/2022/formulas/mathematics/high-school/8q12tzqvloj7lcgvymweqpg900chp7edck.png)
![(a^n)/(a^m) = a^(n - m)](https://img.qammunity.org/2022/formulas/mathematics/high-school/1ftco1d1adkn1mh7qdd28koefqs49c7mas.png)
Using these in the quotient equation we get:
![(f(x + 1))/(f(x)) = (3^(x + 1))/(3^x) = (3^x*3^1)/(3^x) = (3^x)/(3^x)*3 = 1*3 = 3](https://img.qammunity.org/2022/formulas/mathematics/high-school/korkluq9n6tabqmm8g856qwcubayu2oclj.png)
Then:
![(f(x + 1))/(f(x)) = 3](https://img.qammunity.org/2022/formulas/mathematics/high-school/v3vcfgy1dx53hcpt7fdrypjeitgkt7isg3.png)
![f(x + 1) = 3*f(x)](https://img.qammunity.org/2022/formulas/mathematics/high-school/jpju9sguz2s61gt6yojmsez03mkvmanlpl.png)
So we found that the y-value increases by a factor of 3 between any two points x₂ and x₁ such that: x₂ - x₁ = 1.